An evaluation of financial statements in disclosing true business performance to stakeholders in hospitality industry: a case of African Sun Limited - Katiyo, Malvern (Midlands State University, 2017)
The aim of this project was to evaluate financial statements in disclosing true business performance to stakeholders in hospitality industry. The project appreciates that financial disclosures are important and they are essential in the financial reports of organisations. The research focused on the case study of African Sun Limited. The researcher used descriptive research design and qualitative approach was used to collect data. A population of 180 was the target and a sample of 109 was selected using judgemental sampling or non-probability sampling. Questionnaires and structured interviews were used as the research instruments. Only primary data was used in this research. The questionnaire was designed and distributed from a sample of Major Shareholders, Senior Managers, Junior Managers and Accounts Staff in African Sun Limited. Data gathered was presented, analysed and evaluated so as to aid the understanding of the research findings. Bar graphs and tables were used to present data. The researcher then concluded the project by expressing recommendations to company so as to ensure disclosure of true business performance. The research further appreciated that current developments in International Financial Reporting Standard and Generally Accepted Accounting Standards is an achievement towards disclosure of true business performance to stakeholders.